2020
DOI: 10.3390/nu12092874
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB1 Receptors in the Intestinal Epithelium Are Required for Acute Western-Diet Preferences in Mice

Abstract: The endocannabinoid system plays an important role in the intake of palatable food. For example, endocannabinoid signaling in the upper small-intestinal epithelium is increased (i) in rats after tasting dietary fats, which promotes intake of fats, and (ii) in a mouse model of diet-induced obesity, which promotes overeating via impaired nutrient-induced gut–brain satiation signaling. We now utilized a combination of genetic, pharmacological, and behavioral approaches to identify roles for cannabinoid CB1Rs in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…Several biochemical and molecular assays are common for analyzing eCB system activity including qPCR-based analysis of expression of genes for specific components of the system (e.g., eCB biosynthetic and degradative enzymes) (Argueta et al, 2019;Avalos et al, 2020). Importantly, however, quantitating levels of gene expression does not provide a full -and at times accurate -depiction of the state of eCB system activity.…”
Section: Discussionmentioning
confidence: 99%
“…Several biochemical and molecular assays are common for analyzing eCB system activity including qPCR-based analysis of expression of genes for specific components of the system (e.g., eCB biosynthetic and degradative enzymes) (Argueta et al, 2019;Avalos et al, 2020). Importantly, however, quantitating levels of gene expression does not provide a full -and at times accurate -depiction of the state of eCB system activity.…”
Section: Discussionmentioning
confidence: 99%
“…Selective knockdown of CB1 in adipose tissue [21], the liver [22], or skeletal muscle [23] all prevent diet-induced obesity or hyperphagia. Mice in whom CB1 was selectively knocked down in the intestinal epithelium did not have the preference for a Western style diet (with reduced caloric intake and meal size) normally observed in wild-type mice [24]. In a preclinical model of cachexia, it was recently shown that the potent, selective CB1/CB2 agonist WIN55,212-2 led to a significant reduction in the cachexia index and significantly prevented the cachexia-induced increase in gastric emptying [25].…”
Section: Peripheral Cb 1 Receptorsmentioning
confidence: 99%
“…Argueta and DiPatrizio showed that the hyperphagia in mice given free access to a high-fat and sucrose diet was inhibited by a peripherally restricted CB 1 antagonist [45]. These researchers went on to show that mice in whom CB 1 was selectively knocked down in the intestinal epithelium did not have the preference for the high-fat and sucrose diet [24]. Thus, endogenous activation of CB 1 in the intestine increases the palatability of food through gut-brain communication.…”
Section: Gut-brain Axismentioning
confidence: 99%
“…To test the necessity for CB 1 Rs in the intestinal epithelium in the intake of palatable foods, we developed transgenic mice (Cnr1 tm1 . 1 mrl /Vil-CRE ERT2) that are conditionally deficient in CB 1 Rs in the intestinal epithelium (referred to as IntCB 1 -/-mice) [ 63 ]. Mice were maintained on standard rodent chow low in fats and sugars, then given access for the first time to a palatable western-style diet high in fats and sugars (Research Diets D12079B; 40% kcals from fats and 43% from carbohydrates [ 64 ]), and preferences for western diet were measured.…”
Section: Gut-brain Endocannabinoid Signaling Controls Intake Of Palatable Foodsmentioning
confidence: 99%